Association of pre‐ and post‐natal parental smoking with offspring body mass index: an 8‐year follow‐up of a birth cohort. Issue 2 (18th February 2013) - Florath, I.; Kohler, M.; Weck, M. N.; Brandt, S.; Rothenbacher, D.; Schöttker, B.; Moß, A.; Gottmann, P.; Wabitsch, M.; Brenner, H.
Summary What is already known about this subject Maternal smoking during pregnancy is associated with offspring overweight, but it is still unclear whether this association is due to confounding by parental lifestyle habits or caused by direct effects of intrauterine tobacco smoke exposure. What this study adds Maternal smoking during pregnancy was validated by cord serum cotinine measurements and the offspring body mass index was assessed at various ages. Maternal smoking during pregnancy was significantly associated with offspring body mass index at 8 years of age with a trend for increased body mass index from 4 years of age onwards. Paternal smoking and smoking of both parents at pre‐ and post‐natal periods was positively associated with offspring body mass index, which suggests residual confounding by lifestyle habits in smoking families rather than intrauterine effects. Background Although many epidemiological studies have shown an association between maternal smoking during pregnancy and offspring overweight, it is still under debate whether intrauterine tobacco smoke exposure directly affects offspring obesity or if the association is rather due to confounding by lifestyle factors. Objectives The association of parental smoking habits at pre‐ and post‐natal periods with offspring body mass index (BMI) was investigated, whereas maternal smoking during pregnancy was validated by cord serum cotinine measurements. Methods Multivariable linear regression analysis, based on the German Ulm Birth Cohort Study of 1045 children born in 2000 with annual/biennial follow‐up until the age of 8 years (n = 609), was conducted. Results BMI of offspring from mothers who smoked during pregnancy and non‐smoking mothers differed significantly at 8 years. Maternal smoking during pregnancy was associated with an increase in BMI of 0.73 kg m−2 [95% confidence interval: 0.21–1.25] in 8‐year‐old children after adjustment for multiple potential confounding variables. Both pre‐ and post‐natal smoking of fathers (0.34 [0.01–0.66]/0.45 [0.08–0.81]) and of both parents (1.03 [0.43–1.63]/0.56 [0.14–0.98]) were likewise significantly associated with offspring BMI. Conclusions The observed patterns suggest that residual confounding by living conditions in smoking families rather than specific intrauterine exposure to tobacco smoke may account for the increased risk of offspring overweight.